Exploring the Practices, Trends, and Future Directions of Forensic Psychology in the Philippines: A Preliminary Study (Asia Pacific Journal of Social and Behavioral Sciences, 2019)
Forensic psychology is an emerging field in the Philippines. In viewhereof, this study investigated the common qualifications and credentialsof working professionals in forensic psychology in the country. Thisincluded the necessary career-related skills, areas of professional practice,ways of engagements, the various issues and challenges faced by thepractitioners, and the necessary improvements for forensic psychology inorder to advance as a professional practice in the country. This descriptivestudy utilized questionnaires in online and printout forms. A total of 35professionals from diverse background engaged in forensic psychologicalpractice participated in this study. Majority (42.86%) were master’s degreeholders with 1 to 5 years of practice (51.43%). Twelve (12) of them wereregistered social workers; five (5) were registered guidance counselors;nine (9) were registered psychologists, and another nine (9) were registered psychometricians. Results revealed that psychological testing skills, clinical strengths, and ethical uprightness are the necessary skills for forensic psychological practice. Meanwhile, the major lines of practices were in VAWC-related cases, child custody evaluations, competency to stand trial, and annulment cases. They practiced through referrals from other professionals. The challenges and issues facing the field were concerns on confidentiality, mental health-related concerns, lack of graduate and postgraduate training, appropriate assessment skills, professional fee concerns, and conflict of interest among and between allied professionals and the referring party. Measures for the professional advancement included relevant trainings and workshops, offering of graduate and post-graduate courses, conduct of local empirical researches, and additional professional certification specifying forensic practice.
Keywords: Forensic settings, law, psychology in the Philippines, forensic psychology